Deradicalizing Salafism in Amanah: A Story of a Traditionalist Muslim Leader in Poso - Mappiasse, Sulaiman (Islamic Studies Review, 2023)
Deradicalization is often the story of the state’s success or the story of an influential national figure. Our story concerns a local leader and two decades of deradicalization work. Aftermath the outbreak of communal conflict, many Poso local Muslims had been radicalized and viewed jihad against the Christians as part of their holy religious duties. When vigorous law enforcement was undertaken in 2007, controversy over the government’s calling to the mujahidin groups in Tanah Runtuh to disengage from violent acts happened. Some refused the demand and left Tanah Runtuh to declare the Mujahidin Indonesia Timur, a new terrorist group, active until 2021 in the region. Many others stayed. Those who stayed have been gradually deradicalized and successfully integrated into society. Without denying the impact of the state security measure and its multiple agent deradicalization programs in Poso, I argue that the deradicalization of this group had not have been possible without the compassionate leadership of Haji Adnan Arsal. This article examines how he mobilized various factions of jihadists during the conflict and gradually contained radicalism within the Amanah after communal violence ceased.